2009
DOI: 10.1007/s10661-009-1040-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of surface water quality of the Ceyhan River basin, Turkey

Abstract: In this study, surface water quality of the Ceyhan River basin were assessed and examined with 13 physico-chemical parameters in 31 stations in 3 months during the period of 2005. Multivariate statistical techniques were applied to identify characteristics of the water quality in the studied stations. Nutrients, Cl- and Na+ affected mostly to the stations of Erkenez 2, Sir 2, and Sir 3 in the ordination diagram of correspondence analysis. Three factors were extracted by principal component analysis, which expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Tanriverdi & Demirkiran (2010), found similar results when studying the quality of surface water in the watershed of the River Ceyhan in Turkey; applying cluster analysis, the waters of the river were divided into three groups which are influenced by human activity (industrial and agricultural).…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Tanriverdi & Demirkiran (2010), found similar results when studying the quality of surface water in the watershed of the River Ceyhan in Turkey; applying cluster analysis, the waters of the river were divided into three groups which are influenced by human activity (industrial and agricultural).…”
Section: Resultsmentioning
confidence: 63%
“…Multivariate statistics along with Principal Component Analysis (PCA) and Cluster Analysis (CA) have been widely used in data from the monitoring of water quality (Singh et al, 2004;Andrade et al, 2008;Fernandes et al, 2010;Tanriverdi & Demirkiran, 2010;Guedes et al, 2012). This type of analysis reduces the observational data and allows the interpretation of various components individually, since it can indicate associations between samples and/or variables, and also allows identification of possible factors and sources which influence the water system (Bouza-Deaño et al, 2008;Palácio et al, 2011;Guedes et al, 2012;Varol et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in recent years, there has been an increasing interest by researchers in analyzing such complex data using robust mathematics and statistical techniques, such as fuzzy comprehensive evaluation method (FCA), cluster analysis (CA), discriminant analysis (DA), and principal component analysis/factor analysis (PCA/FA), and absolute principal component score-multiple linear regression (APCS-MLR) [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. A literature review of these methods is described below.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this information, they discovered that sea water intrusion, agricultural and industrial pollution, and geological weathering were responsible for the river pollution for both groups. In addition, Tanriverdi et al [21] applied PCA/FA to analyze and assess the surface water quality of Ceyhan River and suggested that the stations near cities were strongly affected by household wastewater, while the other stations were influenced by agricultural facilities. Moreover, Jha et al [22] identified major pollution sources influencing the physico-chemical variables in Aerial Bay using the FA technique, which included rivulet influx into the bay, land run-off, prevailing biological processes and tidal flow.…”
Section: Introductionmentioning
confidence: 99%
“…Rivers carry the municipal and industrial wastewater and run-off from agricultural land in their vast drainage basins and are the most vulnerable to pollution [2]. Human activities significantly decrease water quality and river inflows contribute pollutants to most riverine wetlands, thereby creating serious ecological problems [3]. For control of pollution effectively and water resources management, interpretation of a large number of monitoring data is required [1].…”
Section: Introductionmentioning
confidence: 99%